2018
DOI: 10.1097/pai.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

MCM3: A Novel Proliferation Marker in Oral Squamous Cell Carcinoma

Abstract: The present study sought to evaluate and compare the immunoexpression of proteins minichromosome maintenance (MCM) 3 and Ki-67 in oral squamous cell carcinoma (OSCC) to assess the potential of these proteins as markers of cellular proliferation. Twenty-eight cases of OSCC, 9 of tumor-free resection margins (TM), and 4 of non-neoplastic oral mucosa (NNM) were subjected to immunohistochemistry to detect the expression of proteins MCM3 and Ki-67. All OSCCs demonstrated positivity for both proteins. In these tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…Some subunits have been studied in HCC, for example, MCM7 is a poor prognostic factor for HCC and promotes HCC growth through activating MAPK signaling [9], MCM6 is a novel serum biomarker for early HCC and promotes HCC metastasis through activating MEK/ERK pathway [10]. MCM3 belongs to MCM2–7 complex, it is a poor prognosis marker for oral squamous cell carcinoma, melanoma, papillary thyroid carcinoma, cutaneous T-cell lymphomas, osteosarcoma, glioma, keratocystic odontogenic tumor, anaplastic astrocytoma and salivary gland epithelial tumors [11–20]. MCM3 is upregulated in prostate cancer tissues samples with bone metastasis, mouse model showed that MCM3 is increased in mesenchymal-derived tumors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some subunits have been studied in HCC, for example, MCM7 is a poor prognostic factor for HCC and promotes HCC growth through activating MAPK signaling [9], MCM6 is a novel serum biomarker for early HCC and promotes HCC metastasis through activating MEK/ERK pathway [10]. MCM3 belongs to MCM2–7 complex, it is a poor prognosis marker for oral squamous cell carcinoma, melanoma, papillary thyroid carcinoma, cutaneous T-cell lymphomas, osteosarcoma, glioma, keratocystic odontogenic tumor, anaplastic astrocytoma and salivary gland epithelial tumors [11–20]. MCM3 is upregulated in prostate cancer tissues samples with bone metastasis, mouse model showed that MCM3 is increased in mesenchymal-derived tumors [21].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] Current efforts increasingly focus on molecular biomarkers, which may make the histologic classification of tumours more accurate and facilitate us in identifying more aggressive cancers, promoting staging revisions, and creating personalized therapy and better clinical outcomes. [32][33][34][35][36] The goal of this study was to identify the prognostic value of certain clotting markers for patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is present during cellular proliferation of normal cells, premalignant and neoplastic cells but absent in cells that are in G0 phase [31]. MCM3, presented in a variety of human tumors, is involved in tumor proliferation [32], diagnosis [33], and prognosis. For example, Hua et al [34] reported that high mRNA expression levels of MCM2 and MCM3 were correlated with a poor outcome and thus might be clinically useful molecular prognostic markers in glioma.…”
Section: Discussionmentioning
confidence: 99%